Creating Sustainable Universities: Organizational Pathways of Transformation - Kang, Le; Xu, Lei (European Journal of Sustainable Development, 2018)
2030 Agenda for Sustainable Development including the SDGs, is being integrated into sustainability strategies, research, teaching, pedagogy, and campus practices, and to position higher education institutions as key drivers for achieving the SDGs. Without universities as the demonstration of sustainable development, individuals and social changes needed for the creation of a sustainable future for mankind will be difficult. Key aspects of conceptualization of a sustainable university and pathways of organizational transformation are identified in this paper based on a comprehensive literature review and cross case analysis. 17 world leading sustainable universities are selected from Australia, China, Canada, United Kingdom, United States and German. Data collection included in-depth interviews, reviews of documentary sources and analysis of routine data and information from offices of sustainability and websites of case universities. The cross case analysis of this paper depicts an effective, responsible and robust governance structure of world leading sustainable universities. The organizational pathways of transformation of sustainable universities have four key management elements: value, strategy, partnership, transparency. Keywords: Sustainable Development; Sustainable University; Organizational Transformation.